Smartcity : Model Ketahanan Siber Untuk Usaha Kecil Dan Menengah - Ika Riswanti Putranti; Anita Amaliyah; Reni Windiani (Jurnal Ketahanan Nasional, 2020)
ABSTRACT This article placed an example of a cyber resilience model for smartcity in the context of smart-economy which was currently vulnerable to various cyber attacks. On the other hand SMEs were very limited in access to the development of networks and resources in building cyber resilience that ensured sustainability and increased the competitiveness of their businesses. Furthermore, this research identified the best practices of other countries, analyzed the readiness of legal instruments in Indonesia, identified the actors involved and analyzed the factors of obstacles in building a model of cyber resilience for SMEs. The result of this study was that security policy was a big theme with strategic principles in the security strategy of both actors and policies. This could help organizations such as MSMEs to identified, assessed and reduced threats in the cyber world.ABSTRAKArtikel ini meletakan contoh model ketahanan siber bagi smartcity dalam konteks smart-economy yang saat ini rentan terhadap berbagai serangan siber. Di sisi lain pelaku UKM sangat terbatas dalam akses pengembangan networking dan sumberdaya dalam membangun ketahanan siber yang menjamin keberlanjutan dan meningkatkan daya saing usahanya.Selanjutnya penelitian ini mengidentifikasi praktik terbaik negara-negara lain, menganalisis kesiapan perangkat hukum di Indonesia, mengidentifikasi aktor yang terlibat dan menganalisis faktor-faktor hambatan dalam membangun suatu model ketahanan siber bagi UKM.Hasil dalam pembahasan kajian ini adalah bahwasanya keamanan siber merupakan sebuah tema besar dengan prinsip-prinsip strategis dalam strategi keamanan baik berupa aktor maupun kebijakan. Hal ini dapat membantu organisasi seperti UMKM untuk mengidentifikasi, menilai, dan mengurangi ancaman dalam dunia siber.